Application of the in-situ stress testing technology for the design of operating pressure of underground gas storage reservoir - Wang, Qun-yi; Shang, Lin; Xin, Chun-yan; Sun, Yan-chun; Gao, Guang-liang; Wang, Miao; Gu, Xiao (Frontiers in Earth Science, 2023)
The appropriate design of the operating pressure of underground gas storages (UGSs) is of great significance to their safe and profitable operation. In situ stress is basic data for determining the upper limit pressure of UGSs, analyzing fault stability in reservoir areas, and evaluating trap tightness. Generally, the design of the upper limit gas injection pressure of UGSs is a comprehensive geomechanical problem. After research and comparison of measurement methods, it is believed that the measurement of in situ stress induced by hydraulic fracturing can accurately obtain the in situ stress value near the wellbore, and having knowledge about the reservoir stress path will considerably decrease the risk of reservoir and cap rock instability during gas injection and production. Taking Well C1, an oil reservoir-type UGS in Block M, eastern China as an example, this paper introduces the use of hydraulic fracturing (HF) in situ stress testing technology to obtain the minimum principal stress values of the caprock, reservoir and floor intervals of Well C1. The measured minimum principal stress of the caprock is 32.8-36.8 MPa. Because it is an old well, the minimum principal stress of the reservoir is 33.7-34.2 MPa after correction of the in situ stress measurement according to the theory of elasticity. Based on the comprehensive analysis of the measured in situ stress data, it is believed that the safe upper limit of the reservoir-type gas storage in Block M is 27.2 MPa.